3,4-DIHYDROXYBENZOIC ACID AND 3,4-DIHYDROXYBENZALDEHYDE FROM THE FERN Trichomanes chinense L.; ISOLATION, ANTIMICROBIAL AND ANTIOXIDANT PROPERTIES - Nova Syafni; Deddi Prima Putra; Dayar Arbain (Universitas Gadjah Mada, 2012)
3,4-dihydroxybenzoic acid (1) and 3,4-dihydroxybenzaldehyde (2) have been isolated from ethyl acetate fraction of methanolic fractions of leaves, stems and roots of the fern Trichomanes chinense L. (Hymenophyllaceae). These two compounds also showed significant antioxidant using DPPH and antimicrobial activities using the disc diffusion assay.